Effect and mechanism of ureido-modified MQ silicone resin and platinum on tracking and erosion resistance of silicone rubber. (September 2018) - Chen, Wanjuan; Zeng, Xingrong; Lai, Xuejun; Li, Hongqiang; Pan, Zhijie
Abstract: How to effectively enhance the tracking and erosion resistance of silicone rubber is a significant topic in high-voltage insulation. In this work, ureido-modified MQ silicone resin (UHMQ) was synthesized and employed to improve tracking and erosion resistance of silicone rubber in combination with platinum (Pt). The effect and mechanism of UHMQ/Pt on tracking and erosion resistance were studied via inclined plane test, leakage current curves, scanning electron microscopy, thermogravimetry and thermogravimetry-Fourier transform infrared spectrometry. When 5–7 phr of UHMQ and 0.33 phr of Pt catalyst were added, the tracking and erosion resistance of silicone rubber were greatly improved. In this case, all specimens passed the inclined plane test at 4.5 kV with low eroded mass and undamaged surfaces. The thermal stability of silicone rubber containing UHMQ/Pt was also much higher than that without, and the leakage current and discharging frequency on the surface of silicone rubber were markedly decreased with the introduction of UHMQ/Pt. This was attributed to UHMQ/Pt catalyzing radical crosslinking of silicone chains under arc discharging so that a protective barrier was established on the surface to resist arc ablation. Also, the enhanced radical mechanism suppressed degradation of silicone chains, and thus reduced release of cyclic oligomers which would aggravate arc discharging. Furthermore, since UHMQ/Pt facilitated complete oxidation of pyrolysis gases, the carbon deposit was reduced and tracking was suppressed. Highlights: Ureido-modified MQ silicone resin (UHMQ) and platinum (Pt) were introduced into silicone rubber. UHMQ/Pt could significantly improve the thermal stability and tracking and erosion resistance of silicone rubber. UHMQ/Pt reduced average leakage current and discharging frequency on the surface of silicone rubber. The TG-FTIR of evolved gases during heating was performed. The possible suppression mechanism of UHMQ/Pt on tracking and erosion of silicone rubber was proposed.